2002
DOI: 10.1091/mbc.02-02-0029
|View full text |Cite
|
Sign up to set email alerts
|

The Small GTPase Rab13 Regulates Assembly of Functional Tight Junctions in Epithelial Cells

Abstract: Junctional complexes such as tight junctions (TJ) and adherens junctions are required for maintaining cell surface asymmetry and polarized transport in epithelial cells. We have shown that Rab13 is recruited to junctional complexes from a cytosolic pool after cell-cell contact formation. In this study, we investigate the role of Rab13 in modulating TJ structure and functions in epithelial MDCK cells. We generate stable MDCK cell lines expressing inactive (T22N mutant) and constitutively active (Q67L mutant) Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
68
2
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(81 citation statements)
references
References 46 publications
9
68
2
2
Order By: Relevance
“…The paracellular flux assay was as described in Marzesco et al (2002). Briefly, MDCK cells were cultured in duplicate for 5 d to reach the steady state in 24-mm Transwells.…”
Section: Measurement Of Transepithelial Electrical Resistance (Ter) Amentioning
confidence: 99%
“…The paracellular flux assay was as described in Marzesco et al (2002). Briefly, MDCK cells were cultured in duplicate for 5 d to reach the steady state in 24-mm Transwells.…”
Section: Measurement Of Transepithelial Electrical Resistance (Ter) Amentioning
confidence: 99%
“…Although this approach must be treated cautiously because the behavior of the transfected protein may be altered by overexpression and/or addition of GFP, it has proved useful in the study of numerous Rab proteins, including the closely related Rab8 (Ang et al, 2003), Rab13 (Marzesco et al, 2002), and yeast Sec4p (Schott et al, 2002). Although abnormal behaviors induced by overexpression cannot be excluded, our morphological and kinetic analyses demonstrated that cells expressing a GFP chimera of the wild-type Rab10 behaved very similarly to untransfected cells and that the effects of the different GFP-Rab10 constructs were consistent over a wide range of expression levels and were restricted to a subset of membrane transport pathways.…”
Section: Rab10mentioning
confidence: 99%
“…Like Sec4p, Rab8 and Rab13 have also been associated with polarized membrane transport. Rab8 has been found to regulate transport from the TGN to the basolateral membrane of polarized MDCK cells (Huber et al, 1993;Ang et al, 2003), and both Rab8 and Rab13 have been associated with junctional complex dynamics in epithelial cells (Zahraoui et al, 1994;Marzesco et al, 2002;Lau and Mruk, 2003;Kohler et al, 2004;Morimoto et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Claudin-1 is another key component of tight junctions typically detected along the lateral membranes between neighboring cells. 23 As shown in Fig. 1F (x-y and x-z images), incubating RPG cells with antibody to claudin-1 labeled the lateral membranes.…”
Section: Morphological Characterization Of Rhesus Parotid Epithelial mentioning
confidence: 78%